EFFECTS OF GA3, NAA AND BA SUPPLEMENTATION TO THE MATRIX OR IN CULTURE MEDIUM ON GERMINATION OF ARTIFICIAL SEEDS OF PANAX VIETNAMENSIS HA ET GRUSHV. - Trinh Thi Huong, Vu Quoc Luan, Nguyen Phuc Huy (2023)
11(4)